High‐Performance Static Induction Transistors Based on Small‐Molecule Organic Semiconductors. Issue 9 (15th July 2020) - Guo, Erjuan; Xing, Shen; Dollinger, Felix; Wu, Zhongbin; Tahn, Alexander; Löffler, Markus; Leo, Karl; Kleemann, Hans
Abstract: The polymeric organic‐static‐induction transistor (OSIT), a solid‐state vacuum triode, has been extensively studied as a promising vertical organic thin‐film transistor. By utilizing polymers as organic semiconductors in OSITs, important performance figures have been achieved, for example, a maximum on‐current output of about 10 mA cm −2, on/off current ratio as high as 10 5, and a large current gain of 1000. However, even though polymers with higher mobility have been developed, the performance of OSITs has not been significantly improved yet. In this work, record‐high performance OSITs with small‐molecule materials as organic semiconductors are demonstrated. Pentacene as a hole‐transport material for p‐type OSITs can be easily deposited into pinholes of the gate electrode, hence creating effective conducting channels. Excellent characteristics, such as a high on‐current greater than 260 mA cm −2, on/off current ratio up to 3.3 × 10 5, and a large transmission factor of 99.98% as well as high current gain of 7965, are attained. These results make the small‐molecule organic semiconductor a candidate material for vertical OSITs as well as for organic electronics. Abstract : Organic‐static‐induction transistors (OSITs) are demonstrated with record‐high performance by using p‐type small‐molecule organic semiconductors for the first time, providing an uncomparable advantage of pentacene evaporated by the vapor deposition technique. The excellent device performance is ascribed to the high quality of the porous gate electrodes. This work lays a foundation for the integration of OSITs in complex electronic circuits.